The Influence of Product Innovation, Marketing Capabilities, and Brand Equity on The Competitiveness of Herbal Products at PT Keloria Moringa Jaya, Medan - Arif Jonathan P Sihotang; Sondang Nibulan Marbun; Toman Panggabean (Manajemen: Jurnal Ekonomi, 2026)
This study aims to determine and analyze the effect of Product Innovation, Marketing Capability, and Brand Equity on the Competitiveness of Herbal Products at PT Keloria Moringa Jaya, Medan. The research method used in this study is a quantitative descriptive research method. The number of samples in this study was 70 respondents, calculated using a formula with a 10% margin of error. Based on the results of the t-test hypothesis, it can be concluded that product innovation partially has a positive and significant effect on product competitiveness, marketing capabilities partially do not have a significant effect on product competitiveness, and brand equity partially has a positive and significant effect on product competitiveness. Based on the results of the F hypothesis test, it can be concluded that product innovation, marketing capabilities, and brand equity together or simultaneously have a significant effect on product competitiveness. Based on the results of the coefficient of determination analysis, it is known that the coefficient of determination (adjusted R-square) value is 0.671. Based on this value, product innovation, marketing capabilities, and brand equity are able to influence purchasing decisions by 67.1%, with the remaining 32.9% explained by other variables or factors